Multifractal scaling of flux penetration in the Iron-based Superconductor Ba(Fe0.925Co0.075)2As2 - Grisolia, Mathieu; Van Der Beek, Cornelis Jacominus; Fasano, Yanina; Forget, Anne; Colson, Dorothée (American Physical Society, 2013)
Fil: Grisolia, Mathieu. Ecole Polytechnique; Francia